Dead of winter - Jones, Stephen Mack (The August Snow novels, 2021)
"Authentico Foods Inc. has been a part of Detroit's Mexican town for over thirty years, grown from a home kitchen business to a city-block-long facility that supplies Mexican tortillas to restaurants throughout the Midwest. Detroit ex-cop and Mexican town native August Snow has been invited for a business meeting at Authentico Foods. Its owner, Ronaldo Ochoa, is dying, and is being blackmailed into selling the company to an anonymous entity. Worried about his employees, Ochoa wants August to buy it. August has no interest in running a tortilla empire, but he does want to know who's threatening his neighborhood. Quickly, his investigation takes a devastating turn and he and his loved ones find themselves ensnared in a dangerous net of ruthless billionaire developers. August Snow must fight not only for his life, but for the soul of Mexican town itself"--